A criação de ostra na Paraíba, Brasil - Cavalcanti, Andréa Bezerra (2013)
The coast of Paraíba has an unquestionable environmental and aquaculture potential, where the creation of native oyster species is carried out by estuarine fishing communities. Oysters fattening is an extractive activity in the process of becoming a sustainable alternative for income. This research seeks to inaugurate an investigation on Oyster Breeding, with an on-site study in the Mamanguape River Estuary, being the starting point for species conservation measures and support for the management and monitoring plan of the Estuary APA Conservation Unit Mamanguape River and other mangroves. It is intended, therefore, to know the local practices, generate contributions to the sustainability of the activity in Paraíba and develop new experiments in fattening in captivity, outside the mangrove, with the aim of producing organic oysters, free from contaminants. It is understood that addressing such issues can facilitate dialogue between the scientific community and the traditional community, generate results - the basis for monitoring, public policies for fishermen, in addition to inciting research on the support and recomposition capacity of the mangrove and oysters. In Paraíba, the oyster culture business is proving insipient, waiting for a market opening, quite discouraged by the lack of guarantee of the quality of the fish. The investigation also showed that the producers use the suspended, immersed technique, of the Galilean type, hanging on wooden stakes in the mangrove. The main collection points today are Gamboas of Macacos, Mero and Brejinho. Pillow systems are used in shallow areas, punishment is the technique indicated as ideal to prevent scale. The laboratory experiment allowed us to conclude that keeping oysters in captivity is feasible for a period and, as long as there is sufficient production of live food, you can test the fattening. It is important to continue this research, so that a more sustainable production of oysters is possible.